Giving Theory A Life: First Year Student Conceptions of Legal Theory - Mary Keyes; Graeme Orr (Legal Education Review)
This paper presents findings of interviews conducted with a diverse selection of first year law students to gauge their conceptions of “legal theory”. It does so against the backdrop of a long-standing debate about the nature and purpose of the legal theory taught in the undergraduate LLB. In doing so, it maps out the surprisingly varied and complex perceptions and understandings of legal theory that students can develop, after less than one year of a law course that attempts to integrate the teaching of theoretical and doctrinal material. These findings bear out the animistic assessment of one of the students, that legal theory has “got a life.